Intellectual developmental disorder with hypertelorism and distinctive facies (IDDHDF) A case study with literature review - Nget, Kimseang; Min, Zhu (PT. Riset Press International, 2024)
The research aims to investigate the clinical manifestations of neurodevelopmental problems in children with different facies and CCNK gene mutant characteristics. A literature study was carried out to identify the role of CCNK mutations in IDDHDF. Chinese and international search engines like PubMed, MEDLINE, Wanfang Data Knowledge, and Google Scholar were used to search. The search phrases